Nutrient Value of Leaf vs. Seed - Edelman, Marvin; Colt, Monica (Frontiers in Chemistry, 2016)
Major differences stand out between edible leaves and seeds in protein quality, vitamin and mineral concentrations and omega 6 / omega 3 fatty acid ratios. Data for seeds (wheat, rice, corn, soy, lentil, chick pea) are compared with corresponding data for edible green leaves (kale, spinach, broccoli, duckweed). An x/y representation of data for lysine and methionine content highlights the group differences between grains, pulses, leafy vegetables and animal foods. Leaves come out with flying colors in all these comparisons. The perspective ends with a discussion on “So why do we eat mainly seeds?”